Intensity and pace calculation of Ultra Short Race Pace Training (USRPT) in swimming—take-home messages and statements for swimming coaches - Papadimitriou, K. (Sports, 2024)
A recently referenced method known as ultra short race pace training (USRPT), designed to familiarize swimmers with the pace of a swimming event by using high volumes and submaximal intensities, has emerged as an efficient approach, enhancing performance and predicting swimming outcomes. Despite its recognized benefits, particularly its lower physiological burden compared to other training methods, research on USRPT is still in its early stages. There are misunderstandings related to its intensity and the pace of calculation. This systematic review aims to provide valid statements identifying the pros and cons of USRPT as a training stimulus and providing swimming coaches with key messages and advice about this training method. For the analysis, 90,612 studies from PubMed, EBSCO, Science Direct, and Google Scholar databases were screened to research the background, intensity, and pace calculation of the USRPT method, although only four met the inclusion criteria. The final screening of the selected studies was conducted using a PRISMA-P document. USRPT has the potential to become a dominant training stimulus, offering a precise alternative to the often vague training sets that many swimmers use. However, further studies focusing on specific aspects of intensity and pace calculation within USRPT sets are needed for comprehensive understanding. In conclusion, USRPT appears to be a submaximal variation of high-intensity interval training (HIIT) with low blood lactate relevance to swimming events. Also, the pace calculation must be implemented considering the different demands of each point of a swimming event.